Operation of the Atypical Canonical Bone Morphogenetic Protein Signaling Pathway During Early Human Odontogenesis - Hu, Xiaoxiao; Lin, Chensheng; Ruan, Ningsheng; Huang, Zhen; Zhang, Yanding; Hu, Xuefeng (Frontiers in Physiology, 2022)
BMP (bone morphogenetic protein) signaling plays essential roles in the regulation of early tooth development. It is well acknowledged that with binding of extra-cellular BMP ligands to the type I and type II transmembrane serine/threonine kinase receptor complexes when triggering of the BMP canonical signaling pathway, receptor activated Smad1/5/8 in cytoplasm bind to Smad4, the central mediator of the canonical BMP signaling pathway, to form transfer complexes for entering the nucleus and regulating target gene expression. However, a recent study revealed the functional operation of a novel BMP mediated signaling pathway named as the atypical BMP canonical signaling pathway in mouse developing tooth, which is Smad1/5/8 dependent but Smad4 independent. In the current study, we investigated whether this atypical BMP canonical signaling is conserved in human odontogenesis. We showed that pSmad1/5/8 is required for expression of MSX1, a well-defined BMP signaling target gene, in human dental mesenchyme, but the typical BMP canonical signaling is indeed not operating in the early human developing tooth, as evidenced by the absence of pSMAD1/5/8-SMAD4 complexes in the dental mesenchyme and translocation of pSMAD1/5/8 and expression of MSX1 induced by BMP4 is SMAD4-independent in human dental mesenchymal cells. Moreover, integrative analysis of RNA-Seq data sets comparing the transcriptome profiles of human dental mesenchymal cells with and without SMAD4 knockdown by siRNA displays un-changed expression profiles of pSMAD1/5/8 downstream target genes, further affirming the functional operation of the atypical canonical BMP signaling pathway in a SMAD1/5/8-dependent but SMAD4-independent manner in the dental mesenchyme during early odontogenesis in humans.